2018
DOI: 10.1186/s40364-018-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

PI3K, p38 and JAK/STAT signalling in bronchial tissue from patients with asthma following allergen challenge

Abstract: BackgroundInhaled allergen challenges are often used to evaluate novel asthma treatments in early phase clinical trials. Current novel therapeutic targets in asthma include phosphoinositide 3-kinases (PI3K) delta and gamma, p38 mitogen-activated protein kinase (p38) and Janus kinase/Signal Transducer and Activator of Transcription (JAK/STAT) signalling pathways. The activation of these pathways following allergen exposure in atopic asthma patients it is not known.MethodsWe collected bronchial biopsies from 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…119 All these signaling pathways have been implicated in asthma and mediate critical functions within the airway structural cells. [120][121][122][123][124][125] It is of note that even though the elucidated targets of miR-1 provide a coherent molecular mechanism for its effect on tissue eosinophilia, these findings do not rule out a direct effect of miR-1 on the intrinsic signaling events within eosinophils. There are limitations to our investigation.…”
Section: Discussionmentioning
confidence: 93%
“…119 All these signaling pathways have been implicated in asthma and mediate critical functions within the airway structural cells. [120][121][122][123][124][125] It is of note that even though the elucidated targets of miR-1 provide a coherent molecular mechanism for its effect on tissue eosinophilia, these findings do not rule out a direct effect of miR-1 on the intrinsic signaling events within eosinophils. There are limitations to our investigation.…”
Section: Discussionmentioning
confidence: 93%
“…Dose-response studies to explore the effect of lower doses of LAS194046 on pSTAT6 showed that 0.3 and 1 mg/kg had similar significant effects. Increase of several pSTATs has been reported in the literature in human airway of patients with asthma and COPD (Christodoulopoulos et al, 2001;Mullings et al, 2001; Yew-Booth et al, 2015), proving relevance Profile of the New Inhaled Pan-JAK Inhibitor LAS194046 of the JAK-STAT pathway in those diseases and the potential for these proteins to be used as target engagement markers in clinical studies (Southworth et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…pAKT is an important biomarker for human cancer [22][23][24][25]. To establish pAKT as a direct phosphorylation target of MER kinase, we developed a MER cellular assay and compared the inhibition of MER activation and AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 99%